Altered processing of sweet taste in the brain of diet soda drinkers - Green, Erin (2012)
Artificially sweetened beverage consumption has been linked to obesity, and it has been hypothesized that considerable exposure to nonnutritive sweeteners may be associated with impaired energy regulation. The reward system plays an integral role in modulating energy intake, but little is known about whether habitual use of artificial sweetener (i.e., diet soda consumption) may be related to altered reward processing of sweet taste in the brain. To investigate this, we examined fMRI response after a 12-hour fast to sucrose (a nutritive sweetener) and saccharin (a nonnutritive sweetener) during hedonic evaluation in young adult diet soda drinkers and non-diet soda drinkers. Diet soda drinkers demonstrated greater activation to sweet taste in the dopaminergic midbrain (including ventral tegmental area) and right amygdala. Saccharin elicited a greater response in the right orbitofrontal cortex (Brodmann Area 47) relative to sucrose in non-diet soda drinkers. There was no difference in fMRI response to the nutritive or nonnutritive sweetener for diet soda drinkers. Within the diet soda drinkers, fMRI activation of the right caudate head in response to saccharin was negatively associated with the amount of diet sodas consumed per week; individuals who consumed a greater number of diet sodas had reduced caudate head activation. These findings suggest that there are alterations in reward processing of sweet taste in individuals who regularly consume diet soda, and this is associated with the degree of consumption. These findings may provide some insight into the link between diet soda consumption and obesity.